A new method for solving power flow problem in low voltage islanded microgrids based on loss control in generation units (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Conventional power flow methods could not be used in islanded microgrids (IMGs) because the reference bus frequency and voltage are assumed to be constant. Usually, the presumptions of the power flow problem cannot be generalized to the intended characteristics of an islanded microgrid, and all distributed generators (DGs) play their role in providing active and reactive power to keep the frequency constant in a microgrid. Under such a situation, the problem should be modeled without the reference bus and taking into account the steady-state frequency and the reference bus voltage as a power flow variable. In this case, parameters such as load and line admittance change with changing frequency in every iteration, affecting the convergence of such networks and increasing the number of iterations. To reduce the number of iterations in such networks, new mathematical methods, such as the Levenberg–Marquardt method, are used.By using a new equation for calculating various values voltages and angles as well as presenting and calculating coefficients to reduce iterations, this method speeds up the process of solving the power flow problem. The new method performs the calculations regarding power flow by approximating the first-order solution from the Jacobin matrix. It has also speeded up the solution process by calculating the coefficients of the power differences at each stage.